1997
DOI: 10.1016/s0266-7681(97)80060-5
|View full text |Cite
|
Sign up to set email alerts
|

Day Care Surgery for Advanced Dupuytren’s Contracture

Abstract: Seventy-six consecutive patients suffering from advanced Dupuytren's contracture were analysed in order to evaluate the safety of day care surgery. The complication rates for haematoma, necrosis, infection and reflex sympathetic dystrophy were acceptable, but we found an unacceptably high percentage of nerve lesions. Day care treatment was achieved in all but seven cases. We concluded that advanced Dupuytren's contracture can be treated by day care surgery but the operations should be performed by surgeons who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…Robins et al 18 had no nerve lesions in 50 primary cases, and Makela et al 8 had an incidence of 1%. Ebskov et al 16 found an incidence of 9.6% in 52 primary cases and 4.2% in recurrent cases. For the minor complications, differences between primary and recurrent surgery could not be found.…”
Section: Discussionmentioning
confidence: 95%
“…Robins et al 18 had no nerve lesions in 50 primary cases, and Makela et al 8 had an incidence of 1%. Ebskov et al 16 found an incidence of 9.6% in 52 primary cases and 4.2% in recurrent cases. For the minor complications, differences between primary and recurrent surgery could not be found.…”
Section: Discussionmentioning
confidence: 95%
“…A small percentage (1%) was represented by trauma surgeons [11]. In a 6-month study of 76 consecutive Danish patients with advanced Dupuytren's disease, day case surgery was performed on 96% (50/52) of patients with primary contracture and 79% (19/24) of those with recurrent disease [12]. Senior registrars from the Department of Orthopaedic Surgery performed 89% of primary surgeries and 50% of recurrent surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Reported complication rates for surgical fasciectomy have been reported from 17% to 29%. 11,12,16,17 Hematoma and skin necrosis remain the most common complications, and nerve injury rates range from 0% to 9.6%. 12,17-19 Disease recurrence following palmar fasciectomy ranges from 41% to 54% at 5 years, 7-9 and 15% of these patients will require reoperation to address disease recurrence.…”
Section: Discussionmentioning
confidence: 99%